Data Sheet 2_Enhancing tobacco quality and flavor through cold plasma treatment: structural, chemical, and sensory modifications.xlsx - Xiujuan Xu (8810141) (2025)
Cold plasma (CP) treatment has emerged as a promising green processing technology for enhancing the quality of tobacco by modifying its physical structure and chemical composition. This study investigated the effects of CP on Zimbabwe and Yunnan tobacco, focusing on its impact on sensory attributes, microstructure, and molecular composition. CP treatment, optimized at 100 kV for 1 min, enhances both the aroma and smoke smoothness, increasing sensory scores from 6 to 7. Scanning electron microscopy (SEM) revealed that CP treatment induced surface disruption, creating irregular pores and increasing the pore density, which could enhance drying kinetics. Nontargeted metabolomics analysis reveals 43 putatively annotated metabolites which are significantly varied after CP treatments (i.e., fold change >3 and q-value <0.05), which correlated with improved sensory characteristics. Among these annotated compounds, substantial changes in the lipidomic profile is identified, with specific reductions in highly unsaturated and ether-linked phospholipids. These findings suggest that CP treatment selectively modifies surface lipids, potentially improving tobacco flavor by reducing harshness and enhancing aroma release. Furthermore, the study confirmed the role of CP in reducing excess surface lipids, as demonstrated using soy lecithin-doped tobacco as a model system. Overall, CP offers significant potential for enhancing tobacco flavor and quality, with implications for more sustainable and efficient post-harvest processing.